STRATEGI PENGEMBANGAN BISNIS PADA UMKM KONVEKSI SERAGAM MENGGUNAKAN BUSINESS MODEL CANVAS DAN ANALISIS SWOT - Hilmi Aulawi; Risa Aisyah; Edi Kurniawan (ITB AAS INDONESIA, 2023)
This study aims to map current and future businesses through the Business Model Canvas and design business development strategies on uniform convection using SWOT Analysis. The method used is descriptive qualitative research with Business Model Canvas analysis techniques and SWOT Analysis. The study respondents as many as eight people were selected using the probability sampling method with purposive sampling technique. The results of this study are improvements to the mapping of the current Business Model Canvas which includes nine elements and the results of a SWOT Analysis regarding the design of business development strategies from the Business Model Canvas. The results of the SWOT analysis provide an overview of the company's condition in quadrant I, which means it can carry out business development by utilizing existing strengths and opportunities. In improving the Business Model Canvas for the future with the results of the SWOT analysis strategy, it is recommended to carry out an S-O strategy, by maximizing product marketing, building relationships with several partners and maintaining good consumer relations by utilizing social media, opening stores independently by providing discounts that have registered members, while maintaining the quality of materials by setting relative prices.